A battery configuration method based on negative electrode stable halide solid electrolyte
By adopting a battery configuration method based on the negative electrode stable halide solid electrolyte in all-solid state batteries, the problems of unstable halide solid electrolyte on lithium metal negative electrodes and high cost of sulfide solid electrolyte are solved, and a solid electrolyte with high ionic conductivity and low cost are achieved, and the commercialization of all-solid state batteries is promoted.
Patent Information
- Application Number
- CN202411962202.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-01
AI Technical Summary
The existing halide solid electrolytes are unstable to lithium metal negative electrodes, limiting their application space, and the high cost of sulfide solid electrolytes hinders the commercialization of all-solid state batteries.
Using a battery configuration method based on the negative electrode stable halide solid electrolyte, solid electrolyte materials with high ionic conductivity and high negative electrode stability are prepared as a substitute for sulfide solid electrolytes by premixing LiX and MeXn in a stoichiometric LiaMebX6, high-speed ball milling, post-annealing treatment (if necessary) and compacting.
Solid-state electrolytes with high ionic conductivity, low cost and high negative electrode stability are achieved, reducing the cost of all-solid-state batteries and promoting their commercial application.
Smart Images

Figure CN119742461A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of all-solid-state batteries, and in particular relates to a battery configuration method based on a negative electrode stable halide solid electrolyte. Background Art
[0002] All-solid-state batteries are considered to be the next form of traditional commercial lithium batteries due to their high energy density and safety. However, what kind of solid electrolyte can be truly applied to commercial all-solid-state batteries remains unresolved. Oxide solid electrolytes require high-temperature sintering, which is time-consuming and energy-consuming, while sulfide solid electrolytes are expensive and have poor stability. In recent years, the new halide solid electrolyte reported by Panasonic Corporation of Japan has attracted worldwide attention as a new solid electrolyte development route (Adv. Mater. 2018, 30, 1803075).
[0003] The halide solid electrolyte with chloride ions as the anion framework not only has an ionic conductivity comparable to that of the sulfide solid electrolyte, but also has a higher oxidation potential that can support its direct contact with a high-voltage positive electrode above 4V. In addition, when the structural cation of the halide solid electrolyte is Zr 4+ Its ultra-low preparation cost greatly reduces the cost of all-solid-state batteries (Nat. Commun. 2021, 12, 4410). 4+ Due to the instability of the lithium metal negative electrode, it cannot directly contact the lithium metal negative electrode. This greatly limits its application space. In practical applications, a layer of sulfide solid electrolyte must be added between the lithium zirconium chloride and the lithium metal (or other alloys such as lithium indium alloy) negative electrode as a buffer layer. This is because the solid electrolyte interphase (SEI) generated by the in-situ reaction at the interface between the sulfide solid electrolyte and the negative electrode has a self-limiting effect, which can prevent further reaction (ACS Energy Lett. 2021, 6, 9, 3261–3269). However, due to the high price limit of sulfide solid electrolytes, even if the lithium zirconium chloride type halide solid electrolyte meets the economic requirements, the cost of all-solid-state batteries is still difficult to reduce to a full commercial level. Summary of the invention
[0004] The object of the present invention is to solve the above problems and provide a battery configuration method that uses a solid electrolyte with high ionic conductivity, high economy and high negative electrode stability as a negative electrode intercalation to expand the options of electrolyte combination.
[0005] In order to solve the above technical problems, the technical solution of the present invention is: a battery configuration method based on a negative electrode stable halide solid electrolyte, comprising the following steps:
[0006] S1. LiX and MeX n According to the stoichiometric Lia Me b Weigh and pre-mix in the form of X6;
[0007] S2, subjecting the premixed mixture to high-speed ball milling;
[0008] S3. Subsequently, the materials of different systems are treated separately. If it is a monoclinic system, post-annealing treatment is required; if it is a trigonal system, post-annealing treatment is not required, and the solid electrolyte material applied to the next step is obtained;
[0009] S4, weighing the halide solid electrolyte powder obtained in the previous step and pressing it into tablets;
[0010] S5. Then, other solid electrolyte materials that meet the compatibility requirements of the positive electrode can be placed and compacted;
[0011] S6, then placing the pre-mixed composite positive electrode thereon for further compaction, the composite positive electrode should include a positive electrode active material, and a conductive agent and a solid electrolyte may be optionally added;
[0012] S7. Then add the negative electrode foil to the other side of the mold and assemble the mold to ensure airtightness.
[0013] Preferably, X in LiX in S1 is one or more of F, Cl, Br, and I, and Me is one or more of Er, Y, Dy, Tm, Sc, d-block elements, or f-block elements, and the premixing includes two mixing methods: hand mixing and low-speed ball milling.
[0014] Preferably, the ball milling jar and ball milling medium used in the ball milling process in S2 are any one of agate, zirconium dioxide, silicon carbide and stainless steel. During the ball milling process, the ball-to-material ratio is between 10:1-50:1, preferably 30:1.
[0015] Preferably, calcination is performed before the S3 post-annealing treatment. During the calcination, the electrolyte sheet is kept in a vacuum or inert atmosphere. The inert atmosphere is Ar, preferably vacuum.
[0016] Preferably, the ionic conductivity of the solid electrolyte material obtained in S3 should be greater than 10 -5 S cm -1 .
[0017] Preferably, the particle size D50 of the solid electrolyte powder obtained in S3 is between 0.01 μm and 1 μm.
[0018] Preferably, the solid electrolyte in S4 needs to be pressed into powder, and the best pressure is 100-500MPa, preferably 150MPa.
[0019] Preferably, the electrolyte material in S5 includes but is not limited to Li3InCl6, Li3YCl6, Li6PS5Cl, any one of which can be selected.
[0020] Preferably, the positive electrode active material in S6 includes but is not limited to NCM series, NCA series, LCO, LFP, any one of which can be selected, and the conductive carbon material in the composite positive electrode material in S6 includes but is not limited to acetylene black, VGCF, CNT, any one of which can be selected, and no conductive agent may be added.
[0021] Preferably, the negative electrode foil used in S7 includes but is not limited to lithium, lithium-indium alloy, lithium-tin alloy, and lithium-aluminum alloy.
[0022] The beneficial effects of the present invention are:
[0023] 1. The present invention provides a battery configuration method based on a negative electrode stable halide solid electrolyte, which has a halide solid electrolyte with high economy, high ionic conductivity and high negative electrode stability as a substitute for the sulfide solid electrolyte interlayer to further reduce the cost of all-solid-state batteries, thereby promoting the full commercialization of all-solid-state battery technology.
[0024] 2. The present invention effectively solves the negative electrode stability problem of most halide solid electrolytes and further reduces the commercialization cost of all-solid-state batteries, which can effectively promote their commercial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The present invention discloses a battery configuration method based on a negative electrode stable halide solid electrolyte, and the ionic conductivity at different temperatures obtained by testing the prepared materials in Example 1 and the fitted Arrhenius relationship thereof.
[0026] Figure 2 This is the constant current cycle test result of the lithium symmetric battery of the halide solid electrolyte prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0027] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments:
[0028] Embodiment 1
[0029] like Figure 1 and Figure 2 As shown, the present invention provides a battery configuration method based on a negative electrode stable halide solid electrolyte, comprising the following steps:
[0030] S1. LiX and MeX n According to the stoichiometric Li a Me b Weigh out and premix in the form of X6.
[0031] In step S1, X in LiX is one or more of F, Cl, Br, and I, and Me is one or more of Er, Y, Dy, Tm, Sc, d-block elements, or f-block elements, wherein the premixing includes two mixing methods: hand mixing and low-speed ball milling.
[0032] In this embodiment, S1, yttrium chloride and lithium bromide are mixed, and pre-mixed by low-speed ball milling in a zirconium oxide ball mill to obtain powder A.
[0033] S2. subjecting the premixed mixture to high-speed ball milling.
[0034] The ball milling jar and ball milling medium used in the ball milling process in step S2 are any one of agate, zirconium dioxide, silicon carbide, and stainless steel. During the ball milling process, the ball-to-material ratio is between 10:1-50:1, preferably 30:1.
[0035] In this embodiment, S2, the powder A obtained in S1 is subjected to high-energy ball milling at a rotation speed of 500 rpm to alloy it.
[0036] S3. Subsequently, the materials of different systems are treated separately. If it is a monoclinic crystal system, post-annealing treatment is required; if it is a trigonal crystal system, no post-annealing treatment is required, and the solid electrolyte material applied to the next step is obtained.
[0037] Before the post-annealing treatment in step S3, calcination is performed, and the electrolyte sheet is kept in a vacuum or inert atmosphere during calcination. The inert atmosphere is Ar, preferably vacuum. The ionic conductivity of the solid electrolyte material obtained in step S3 should be greater than 10 -5 S cm -1 The particle size D50 of the solid electrolyte powder obtained in step S3 is between 0.01 μm and 1 μm.
[0038] In this embodiment, S3, the halide solid electrolyte of the system is monoclinic, and needs to be annealed at a temperature of 450° C. for 5 hours.
[0039] S4. Weigh the halide solid electrolyte powder obtained in the previous step and press it into tablets.
[0040] In step S4, the solid electrolyte needs to be pressed into powder, and the pressure is best at 100-500 MPa, preferably 150 MPa.
[0041] In this embodiment, S4, 60 mg of the halide solid electrolyte powder is placed in a φ10 solid-state battery mold and compacted at a pressure of 1.5 T.
[0042] S5. Other solid electrolyte materials that meet the compatibility requirements of the positive electrode may then be placed and compacted.
[0043] In step S5, the electrolyte material includes but is not limited to Li3InCl6, Li3YCl6, Li6PS5Cl, any one of which can be selected. In this embodiment, S5, 70 mg of Li3InCl6 solid electrolyte is then added and compacted at a pressure of 2T.
[0044] S6. Then, the pre-mixed composite positive electrode is placed thereon for further compaction. The composite positive electrode should include a positive electrode active material, and a conductive agent and a solid electrolyte may be optionally added.
[0045] In step S6, the positive electrode active material includes but is not limited to NCM series, NCA series, LCO, LFP, any one of which can be selected, and the conductive carbon material in the composite positive electrode material in S6 includes but is not limited to acetylene black, VGCF, CNT, any one of which can be selected, and the conductive agent may not be added.
[0046] In this embodiment, S6, the composite positive electrode powder prepared in advance is then added and compacted at a pressure of 3T.
[0047] S7. Then add the negative electrode foil to the other side of the mold and assemble the mold to ensure airtightness.
[0048] The negative electrode foil used in step S7 includes but is not limited to lithium, lithium-indium alloy, lithium-tin alloy, and lithium-aluminum alloy. In this embodiment, S7, a lithium-indium alloy negative electrode is added to the other side, and the mold is assembled to ensure airtightness.
[0049] Embodiment 2
[0050] Compared with the first embodiment, the differences of this embodiment are as follows:
[0051] S1. Mix yttrium chloride and lithium chloride, and pre-mix them by low-speed ball milling in a zirconia ball mill to obtain powder A.
[0052] S2. The powder A obtained in S1 is subjected to high-energy ball milling at a rotation speed of 600 rpm to alloy it.
[0053] S3. The halide solid electrolyte of this system is a trigonal crystal system and does not require annealing treatment.
[0054] S4. Place 40 mg of the halide solid electrolyte powder into a φ10 solid-state battery mold and compact it at a pressure of 1.5 T.
[0055] S5. Then add 60 mg of Li3InCl6 solid electrolyte and compact at a pressure of 2.25T.
[0056] S6. Add the composite positive electrode powder prepared in advance and compact it at a pressure of 3T.
[0057] S7. Add the lithium-indium alloy negative electrode on the other side and assemble the mold to ensure airtightness.
[0058] The rest of this embodiment is the same as the first embodiment.
[0059] Embodiment 3
[0060] Compared with the first embodiment, the differences of this embodiment are as follows:
[0061] S1. Mix erbium chloride and lithium chloride, and pre-mix them by low-speed ball milling in a zirconia ball mill to obtain powder A.
[0062] S2. The powder A obtained in S1 is subjected to high-energy ball milling at a rotation speed of 500 rpm to alloy it.
[0063] S3. The halide solid electrolyte of this system is a trigonal crystal system and does not require annealing treatment.
[0064] S4. Place 40 mg of the halide solid electrolyte powder into a φ10 solid-state battery mold and compact it at a pressure of 1.5 T.
[0065] S5. Then, 90 mg of Li6PS5Cl solid electrolyte was added and compacted at a pressure of 2 T.
[0066] S6. Add the composite positive electrode powder prepared in advance (the active material is LCO coated with lithium niobate) and compact it at a pressure of 3T.
[0067] S7. Add the lithium-tin alloy negative electrode on the other side and assemble the mold to ensure airtightness.
[0068] The rest of this embodiment is the same as the first embodiment.
[0069] Embodiment 4
[0070] Compared with the first embodiment, the differences of this embodiment are as follows:
[0071] S1. Scandium chloride and lithium chloride are mixed, and pre-mixed by low-speed ball milling in a zirconia ball mill to obtain powder A.
[0072] S2. The powder A obtained in S1 is subjected to high-energy ball milling at a rotation speed of 500 rpm to alloy it.
[0073] S3. The halide solid electrolyte of this system is monoclinic, and needs to be annealed. The annealing temperature is 300℃, and the holding time is 5 hours.
[0074] S4. Place 60 mg of the halide solid electrolyte powder into a φ10 solid-state battery mold and compact it at a pressure of 1.5 T.
[0075] S5. Then add 80 mg of Li3InCl6 solid electrolyte and compact it at a pressure of 2.25T.
[0076] S6. Add the composite positive electrode powder prepared in advance and compact it at a pressure of 2.5T.
[0077] S7. Add the lithium-indium alloy negative electrode on the other side and assemble the mold to ensure airtightness.
[0078] The rest of this embodiment is the same as the first embodiment.
[0079] Embodiment 5
[0080] Compared with the first embodiment, the differences of this embodiment are as follows:
[0081] S1. Mix erbium chloride and lithium bromide, and pre-mix them by low-speed ball milling in a zirconia ball mill to obtain powder A.
[0082] S2. The powder A obtained in S1 is subjected to high-energy ball milling at a rotation speed of 450 rpm to alloy it.
[0083] S3. The halide solid electrolyte of this system is monoclinic, and needs to be annealed. The annealing temperature is 450°C, and the holding time is 4 hours.
[0084] S4. Place 60 mg of the halide solid electrolyte powder into a φ10 solid-state battery mold and compact it at a pressure of 1.5 T.
[0085] S5. Then add 75 mg of Li3InCl6 solid electrolyte and compact at a pressure of 2.25T.
[0086] S6. Add the composite positive electrode powder prepared in advance and compact it at a pressure of 3T.
[0087] S7. Add the lithium-indium alloy negative electrode on the other side and assemble the mold to ensure airtightness.
[0088] The rest of this embodiment is the same as the first embodiment.
[0089] Embodiment 6
[0090] Compared with the first embodiment, the differences of this embodiment are as follows:
[0091] S1. Mix holmium chloride and lithium chloride, and pre-mix them by low-speed ball milling in a zirconia ball mill to obtain powder A.
[0092] S2. The powder A obtained in S1 is subjected to high-energy ball milling at a rotation speed of 500 rpm to alloy it.
[0093] S3. The halide solid electrolyte of this system is a trigonal crystal system and does not require annealing treatment.
[0094] S4. Place 70 mg of the halide solid electrolyte powder into a φ10 solid-state battery mold and compact it at a pressure of 2T.
[0095] S5. Then, 70 mg of Li2ZrCl6 solid electrolyte was added and compacted at a pressure of 2.25 T.
[0096] S6. Add the composite positive electrode powder prepared in advance and compact it at a pressure of 2.5T.
[0097] S7. Add the lithium-indium alloy negative electrode on the other side and assemble the mold to ensure airtightness.
[0098] The rest of this embodiment is the same as the first embodiment.
[0099] According to the configuration of ion blocking electrode / solid electrolyte / ion blocking electrode, the room temperature ion conductance of S3 in each embodiment can be further obtained by performing AC impedance test. The calculation formula is, σ=d / (SR), d, S, and R are the measured thickness of the electrolyte sheet, the contact area perpendicular to the electrode interface, and the resistance measured by EIS.
[0100] The solid electrolyte system prepared by the present invention is a white or light gray powder. The solid electrolyte sheet obtained by pressing and molding it exhibits excellent stability to the lithium metal negative electrode, and can replace the traditional sulfide solid electrolyte as an interlayer material between other halide solid electrolytes with poor lithium stability and the negative electrode, thereby supporting a new halide-based all-solid-state battery configuration. The materials involved in the present invention all have a low synthesis cost, which greatly reduces the cost of the halide solid electrolyte route. Because it exhibits high ion transmission capacity and negative electrode stability within the operating temperature range of electronic equipment, it can be applied to solid-state secondary batteries carried by portable electronic devices and electric vehicles.
[0101] Those skilled in the art will appreciate that the embodiments described herein are intended to help readers understand the principles of the present invention, and should be understood that the protection scope of the present invention is not limited to such specific statements and embodiments. Those skilled in the art can make various other specific variations and combinations that do not deviate from the essence of the present invention based on the technical revelations disclosed by the present invention, and these variations and combinations are still within the protection scope of the present invention.
Claims
1. A battery configuration method based on a negative electrode stable halide solid electrolyte, characterized in that: The following steps are involved: S1. LiX and MeX n According to the stoichiometric Li a Me b Weigh and pre-mix in the form of X6; S2, subjecting the premixed mixture to high-speed ball milling; S3. Subsequently, the materials of different systems are treated separately. If it is a monoclinic system, post-annealing treatment is required; if it is a trigonal system, post-annealing treatment is not required, and the solid electrolyte material applied to the next step is obtained; S4, weighing the halide solid electrolyte powder obtained in the previous step and pressing it into tablets; S5. Then, other solid electrolyte materials that meet the compatibility requirements of the positive electrode can be placed and compacted; S6, then placing the pre-mixed composite positive electrode thereon for further compaction, the composite positive electrode should include a positive electrode active material, and a conductive agent and a solid electrolyte may be optionally added; S7. Then add the negative electrode foil to the other side of the mold and assemble the mold to ensure airtightness.
2. A battery configuration method based on a negative electrode stable halide solid electrolyte according to claim 1, characterized in that: In the LiX in S1, X is one or more of F, Cl, Br, and I, and Me is one or more of Er, Y, Dy, Tm, Sc, d-block elements, or f-block elements, and the premixing includes two mixing methods: hand mixing and low-speed ball milling.
3. A battery configuration method based on a negative electrode stable halide solid electrolyte according to claim 1, characterized in that: The ball milling jar and ball milling medium used in the ball milling process in S2 are any one of agate, zirconium dioxide, silicon carbide, and stainless steel. During the ball milling process, the ball-to-material ratio is between 10:1-50:1, preferably 30:
1.
4. A battery configuration method based on a negative electrode stable halide solid electrolyte according to claim 1, characterized in that: Before the S3 post-annealing treatment, calcination is performed. During the calcination, the electrolyte sheet is kept in a vacuum or inert atmosphere. The inert atmosphere is Ar, and vacuum is preferred.
5. A battery configuration method based on a negative electrode stable halide solid electrolyte according to claim 1, characterized in that: The ionic conductivity of the solid electrolyte material obtained in S3 should be greater than 10 -5 S cm -1 .
6. A battery configuration method based on a negative electrode stable halide solid electrolyte according to claim 1, characterized in that: The particle size D50 of the solid electrolyte powder obtained in S3 is between 0.01 μm and 1 μm.
7. A battery configuration method based on a negative electrode stable halide solid electrolyte according to claim 1, characterized in that: The solid electrolyte in S4 needs to be pressed into powder, and the best pressure is 100-500MPa, preferably 150MPa.
8. A battery configuration method based on a negative electrode stable halide solid electrolyte according to claim 1, characterized in that: The electrolyte material in S5 includes but is not limited to Li3InCl6, Li3YCl6, Li6PS5Cl, any one of which can be selected.
9. A battery configuration method based on a negative electrode stable halide solid electrolyte according to claim 1, characterized in that: The positive electrode active materials in S6 include but are not limited to NCM series, NCA series, LCO, and LFP, and any one of them can be selected. The conductive carbon materials in the composite positive electrode material in S6 include but are not limited to acetylene black, VGCF, and CNT, and any one of them can be selected, and the conductive agent may not be added.
10. A battery configuration method based on a negative electrode stable halide solid electrolyte according to claim 1, characterized in that: The negative electrode foil used in S7 includes, but is not limited to, lithium, lithium-indium alloy, lithium-tin alloy, and lithium-aluminum alloy.